Strategi Integrasi Sektor Pertanian dan Perdagangan dalam Pengembangan Klaster Ekonomi Inklusif Kota Sungai Penuh - Rafmil Kurniawan Rafmil Kurniawan (Penerbit Goodwood, 2026)
Purpose: This study aims to formulate an integrated economic policy strategy to promote inclusive and sustainable economic growth in Sungai Penuh City through sectoral integration between agriculture and trade. Research methodology: The study applies an applied policy research approach using secondary data from Statistics Indonesia (BPS), regional planning documents, and local government reports (2020–2024). The analysis includes regional economic assessment, trend analysis, value chain analysis of agriculture–trade linkages, policy evaluation, and comparative analysis of policy alternatives. Results: Agriculture and trade contribute over 40 percent of regional GDP but remain characterized by low productivity and limited value added. Economic growth has not been fully inclusive, as indicated by slow poverty reduction and persistent income inequality. Existing policies are fragmented and sectoral, limiting effective integration among agriculture, trade, and MSMEs. The development of inclusive agricultural–trade economic clusters emerge as the most strategic policy option to strengthen value chains, enhance productivity, expand employment, and improve income distribution. Conclusions: Inclusive and sustainable economic growth in Sungai Penuh City requires an integrated economic policy framework that strengthens sectoral linkages and supports local economic transformation. Limitations: This study relies solely on secondary data without primary or micro-level analysis. Contributions: This study provides an evidence-based policy framework for designing integrated and inclusive regional economic development strategies in non-metropolitan areas.